Analytical Study of Skill Level of Some Contributing Leagues IN Beijing Olympics 2008 IN Wheelchair Basketball - Ahmed, Elaf (Journal of Physical Education, 2012)
Disabled sports witnessed great development in recent years due to their huge importance and effects on society. The researcher, asa coach of youth and advanced wheelchair basketball leagues noticed lack of research that tackles the analytical aspect of this sport. These researches could help detect the variables that affect the nature of sport and their effective role in achieving results. Thus the researcher came up with two questions:1.What are the skill variables that affect game play?2.What are the percentages of success and failure of these variables?The research aimed at identifying the skill variables that affect game play of some participating leagues in Beijing Olympics. In addition to that, it aims at identifying the real level of skill for these leagues.The researcher used the descriptive method. The subjects were selected including Canada, Germany and Iran leagues. Canada league represent America, Germany represent Europe and Iran represent Asia. All defensive and offensive skills were specified. Some results revolved around successful and unsuccessful shots, the total sum of offenses and defenses, the total sum of effective passes as well as the total sum of stealing the ball attempts and transitioning from defense to offence for each league under study.The researcher came up with the following conclusions:-Analysis help in identifying the weaknesses and strengths of leagues to realize the Iraqi league level compared to the competitive leagues.-The length of players played a great role in increasing the number of shooting attempts (defensive and offensive) in all contributing leagues and in the following order Canada, Germany and Iran.-The percentage of successful shooting was as follows Germany, Canada and Iran.-Harmony among players during the game in all leagues contributed in increasing the number of effective passing attempts and respectively Canada, Germany and Iran.Individual skills as well as experience played a great role in stealing the ball for all leagues under study but in the following order Germany, Iran and Canada.